Pengaruh Lingkungan Kerja, Disiplin Kerja Dan Pengawasan Terhadap Kinerja Guru Pada Gugus I Seulanga Raya Subulussalam - Nurhafni Gea (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to determine and analyze the effect of the work environment, work discipline and supervision on the performance of teachers in Cluster I Seulanga Raya Subulussalam. The approach used in this study is an associative approach. The population in this study were all teachers in Cluster I Seulanga Raya Subulussalam. The sample in this study used the slovin formula, amounting to 51 teachers in Cluster I Seulanga Raya Subulussalam. Data collection techniques in this study used questionnaires. The data analysis technique in this study uses Multiple Linear Regression Analysis Test, Hypothesis Testing (t Test), and Coefficient of Determination. The data processing in this study used the SPSS (Statistic Package for the Social Sciences) software program version 24.00. The results of this study prove that partially the work environment has a significant effect on teacher performance, work discipline has a significant effect on teacher performance and supervision has a significant effect on teacher performance and simultaneously the work environment, work discipline and supervision have a significant effect on teacher performance In Cluster I Seulanga Raya Subulussalam.